Bacteriophages – Alternatives to Antibiotics and Beyond - Dhimantkumar V. Bhensdadia; Makasana Atul G. (The Bioscan, 2024)
Bacteriophages are viruses that infect bacterial host and are estimated to be the most numerous biological entities in the biosphere. Phages exist wherever bacteria occur, and share a common ecology with their respective bacterial hosts. They are the most abundant living entities on Earth - the estimates range from 1030 to 1032 in total - and play key roles in regulating the microbial balance in every ecosystem where this has been explored. Medical science has begun to acknowledge the emergency of drug resistant bacteria a fact made more amimous when one realizes that no fundamentally new antibiotic has been discovered for more than 30 years. Are we losing the battle? The emergence of pathogenic bacteria resistant to most, if not all, currently available antimicrobial agents has become a serious and critical problem in modern medicine. The use of host specific bacteriophages has been promoted as an important and cost effective adaptable approach to control zoonotic bacteria.